1970
DOI: 10.1111/j.1476-5381.1970.tb08524.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological significance of biogenic amines in the lungs: histamine

Abstract: Summary . Eight animal species were investigated for the histamine content of the lung and can be divided into two groups: the low‐level group, ranging from 2 to 7 μg/g, consisting of the mouse, rat, guinea‐pig and rabbit; and the high‐level group, ranging from 12 to 35 μg/g, consisting of the cat, dog, goat and human. In two species of the high‐level group (cat and dog) the amount of histamine that elicited an increase in pulmonary resistance was one‐fifth to one‐tenth of the dose that elicited an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A compensatory increase in histamine-forming capacity of tissues has been described in guinea-pig anaphylaxis (Kahlson & Rosengren, 1968) and this may be another possible reason for the failure to observe large changes in calf tissue histamine concentration. Aviado & Sadavongvivad (1970) reported that concentrations of both histamine and 5-HT were increased in the lungs of rabbits after anaphylaxis. We have not observed any such increase in calves.…”
Section: Discussionmentioning
confidence: 99%
“…A compensatory increase in histamine-forming capacity of tissues has been described in guinea-pig anaphylaxis (Kahlson & Rosengren, 1968) and this may be another possible reason for the failure to observe large changes in calf tissue histamine concentration. Aviado & Sadavongvivad (1970) reported that concentrations of both histamine and 5-HT were increased in the lungs of rabbits after anaphylaxis. We have not observed any such increase in calves.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, histamine concentrations in the lung were found to be about 10 times lower than in the initial studies [30,31]. Major strain-specific differences, as observed in the intestine, were absent in the lung, and age-related differences were found in C57Bl/ 6, but not in Balb/c mice.…”
Section: Lungmentioning
confidence: 57%
“…Histamine concentrations in the lung had been analyzed already in 1970 [30], since at that time it was shown that histamine is a central mediator in anaphylaxis, such as in acute allergic asthma. In the present study, histamine concentrations in the lung were found to be about 10 times lower than in the initial studies [30,31].…”
Section: Lungmentioning
confidence: 99%
“…1967). Aviado and Sadavongvivad (1970) showed that the concentrations of both histamine and 5-HT were increased in the lungs of rabbits after anaphylaxis. On the other hand we have not observed elevated histamine or 5-HT concentrations in any bovine tissue following cornpsrand 48/80 treatment (this article) or anaphylaxis (unpublished).…”
Section: Discussionmentioning
confidence: 98%